Analysis of caffeine content in coffee using the indirect method of decaffeination - Nurfatimah Mohd Thani (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Caffeine is one of the worlds most popular psychoactive substances and can be consume in coffee, tea or cocoa. Caffeine is also a naturally occurring substance found in the leaves, seeds or fruits of over 63 plants species worldwide and is an alkaloid of the methylxanthine family. Nevertheless, caffeine has a lot of negative effect, for example reduced bone mass, cardiovascular diseases, depression as well as other hazardous diseases. There are a few methods for coffee decaffeination, one of it is using indirect method, also known as water process. In addition, Design of Expert software is used to analyze the data collected. For indirect method of decaffeination, there are two phases involved, the first one is solid-phase extraction where the parameters involve are temperature of boiling water and time. As for solid-phase extraction, the result obtained shows that the best interaction of parameter is 100 oC for 2 hours with average caffeine concentration of 11.19 mg/L. Moreover, for second phase which involved liquid-liquid extraction, organic solvent used is ethyl acetate. The result shows that the best interaction is 50 % ethyl acetate for 90 minutes with average caffeine concentration of 7.35 mg/L remained after extraction